COLLABORATIVE SERVICE LEARNING: Model Pendidikan Sepanjang Hayat untuk Membina Kepribadian dan Tanggung Jawab Sosial Generasi Digital - Abbas, Sukardi; Nurbaya, Nurbaya (Proceedings of Annual Conference on Community Engagement, 2018)
The digital generation is a generation born in the midst of a digital technology environment. Technology that has changed the way of thinking, learning and working. This generation is under technological pressure so that the information they get more than they can handle and future provisions must be prepared much better than what is maintained. Lifelong learning is the only way to a better future. This is a necessity rather than a possibility to be considered. This article will identify and describe the important elements of lifelong learning by offering a service learning-based collaborative learning model to prepare the present generation (digital generation) who care about the problems that occur in people's lives. collaborative service learning (CSL) exists as a learning model that integrates academic learning and community service.